Gene-wide significant association analyses of DNMT1 genetic variants with Parkinson’s disease - Wang, Jian-Yong; Cui, Lei; Shi, Hong-Yi; Chen, Ling-Hao; Jin, Ren-Wei; Jiang, Xiao-Xia; Chen, Zhu-Ling; Zhu, Jian-Hong; Zhang, Xiong (Frontiers in Genetics, 2023)
Background: DNA methylation plays an important role in Parkinson’s disease (PD) pathogenesis. DNA methyltransferase 1 (DNMT1) is critical for maintaining DNA methylation in mammals. The link between DNMT1 polymorphisms and PD remains elusive. Methods: The DNMT1 gene contained a total of 28 single nucleotide polymorphisms (SNPs). Four representing tag-SNPs (rs16999593, rs2162560, rs11880553, and rs9305012) were identified and genotyped in a Han Chinese population comprising 712 PD patients and 696 controls. Association analyses were performed at gene-wide significance (P < 1.8 × 10-3). Results: Rs9305012, but not the other 3 tag-SNPs, was gene-wide significantly associated with PD risk (P = 0.8 × 10-3). The rs9305012/C was a protective allele against PD (P = 1.5 × 10-3, OR 0.786, 95% CI 0.677-0.912). No significant association was observed in individual genders or PD subtypes. Haplotypes of the 4 tag-SNPs showed a significant overall distribution difference between PD patients and controls (P < 1 × 10-4). The 3-allele ACC module in the order of rs2162560, rs11880553, and rs9305012 was the highest-risk haplotype associated with PD (P < 1 × 10-4, OR 2.439, 95% CI 1.563-3.704). Rs9305012 displayed certain probability to affect transcription factor binding and target gene expression based on functional annotation analyses. Conclusions: The DNMT1 variant rs9305012 together with its haplotypes may gene-wide significantly modulate PD susceptibility. Our results support a role of DNMT1 in PD pathogenesis and provide novel insights into the genetic connection in between.